Correction: Validation of ToucHb, a non-invasive haemoglobin estimation: Effective for normal ranges, needs improvement for anaemia detection. - Yogish Channa Basappa; Sumanth Mallikarjuna Majgi; Shashidhar Byrappa Hanumanahally; Prashanth Nuggehalli Srinivas (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0001541.].